2018
DOI: 10.1123/jpah.2017-0483
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Analysis of the Relationships of Physical Activity and Body Fat With Nerve Growth Factor and Brain-Derived Neural Factor in Children

Abstract: Vigorous physical activity is directly related to serum NGF and indirectly through the level of body fat. The relationships with serum BDNF are more complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…A total of 3612 potentially relevant articles were identified, and, after screening for duplicates, 601 full-text studies were assessed for inclusion after checking titles and abstracts. Finally, 23 studies met the eligibility criteria and were included in the systematic review 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 and 21 in the meta-analysis. The reasons for exclusion based on full texts are reported in Supplementary Material 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 3612 potentially relevant articles were identified, and, after screening for duplicates, 601 full-text studies were assessed for inclusion after checking titles and abstracts. Finally, 23 studies met the eligibility criteria and were included in the systematic review 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 and 21 in the meta-analysis. The reasons for exclusion based on full texts are reported in Supplementary Material 2.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding health-related outcomes, most studies reported data on adiposity, 26 , 27 , 28 , 32 , 34 , 35 , 37 , 38 , 41 , 42 , 43 , 44 , 47 , 48 cardiometabolic risk factors, 26 , 30 , 32 , 35 , 38 bone outcomes, 29 , 31 , 33 , 36 , 39 , 40 , 45 , 46 and health-related physical fitness 27 , 38 , 41 , 48 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the evidences on exercise induced modulation of neurotrophins are related to BDNF analysis (for review see Neeper et al, 1995; Rasmussen et al, 2009; Voss et al, 2013b), a few are related to NGF (Chae et al, 2014; Ando et al, 2016), while works describing the relationship between the two are scarce. In fact, several papers have reported concomitant detection of BDNF and NGF levels changes following exercise (Neeper et al, 1996; Hong et al, 2015; Okudan and Belviranli, 2017; Arvidsson et al, 2018), without addressing the correlation between the two. Only one correlation study, outside the exercise field, was reported in rats, regarding the nervous system development, in which BDNF and NGF show reciprocal behavior during development, but parallel increase in the adult brain (Maisonpierre et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Different types of environmental enrichment, many of which are based on physical activity and exercise, were found to be associated with modulation of proBDNF (Neeper et al, 1995; Ploughman, 2008; Rasmussen et al, 2009; Baroncelli et al, 2010; Sigwalt et al, 2011; Voss et al, 2013a,b). Research related to training-induced dependent changes of neurotrophins is not abundant (Neeper et al, 1996; Hong et al, 2015; Okudan and Belviranli, 2017; Arvidsson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Así mismo, se ha reportado los BDNF en plasma y serum en humanos (Krabbe et al, 2007). Un estudio con niños que se realizó mediante múltiples ensayos en suero, utilizó un análisis en factores de crecimiento (NFG: siglas en inglés) en ese trabajo de investigación se destaca la existencia de una relación longitudinal con respecto a la actividad física vigorosa (Arvidsson, Johannesson, Andersen, Karlsson, Wollmer, Thorsson, & Dencker, 2018). Además, se ha evidenciado que la AF causa un robusto incremento de neurogénesis en el gyrus dentate del hipocampo de humanos (Van Praag, 2008).…”
Section: Estado Actual Del Temaunclassified